2021
DOI: 10.4314/sajee.v36i1.16
|View full text |Cite
|
Sign up to set email alerts
|

The Shifts to Online Learning: Think Piece: Assumptions, Implications and Possibilities for Quality Education in Teacher Education

Abstract: With the advent of coronavirus disease (COVID-19) which has spread to the majority of countries across the world, the World Health Organisation (WHO) declared a global pandemic on 11 March 2020. Governments all over the world, including in southern Africa, introduced measures such as the banning of large gatherings,closure of borders, schools and institutions of higher learning to curb the spread of COVID-19. To ensure ongoing teaching and learning, institutions of higher learning made resolutions to transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Many students struggled to navigate through online learning due to challenges presented by the use of technology (Dube, 2020). Tshiningayamwe, et al (2020) stated that online teaching and learning was relatively new to a number of lecturers and students in southern African countries. A number of studies revealed that the migration to online teaching and learning during COVID-19 offered some challenges (Demuyakor, 2021;Magesa & Josua, 2022;Moluayonge, 2020).…”
Section: Existing Technological Challenges Faced By Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many students struggled to navigate through online learning due to challenges presented by the use of technology (Dube, 2020). Tshiningayamwe, et al (2020) stated that online teaching and learning was relatively new to a number of lecturers and students in southern African countries. A number of studies revealed that the migration to online teaching and learning during COVID-19 offered some challenges (Demuyakor, 2021;Magesa & Josua, 2022;Moluayonge, 2020).…”
Section: Existing Technological Challenges Faced By Studentsmentioning
confidence: 99%
“…Moreover, students also needed to familiarise themselves with online learning platforms or tools, upgrade their computer skills, ensure that they had access to the internet all the time, etc. This was a challenge, as shifting to online came with the assumption that educational institutions had all the capacity and infrastructure necessary to ensure the undisturbed progression of remote/online teaching and learning (Tshiningayamwe et al, 2020). However, this was not the case as explained above.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, both students and teachers can learn and teach at their own pace, which promotes independence and accessibility (Kaisara & Bwalya, 2021). The outcome has been increased enrollment, decreased learning costs, and the achievement of educational objectives and goals in a convenient manner (Tshiningayamwe et al, 2020;Shambare & Simuja, 2022).…”
mentioning
confidence: 99%